Energy Productivity and Environmental Degradation in Germany: Evidence from Novel Fourier Approaches - Addai, Kwaku; Ozbay, Rahmi Deniz; Castanho, Rui Alexandre; Genc, Sema Yilmaz; Couto, Gualter; Kirikkaleli, Dervis (MDPI, 2022)
The increased consumption of fossil fuels worldwide has resulted in unprecedented historic environmental degradation and global warming. According to the United Nations, this is both the defining crisis of our time and a race the world could win given the right policy attention. Researchers seek to find critical pathways to provide policy recommendations for reducing environmental degradation. This paper aims to investigate the effect of energy productivity on environmental degradation in Germany while controlling for economic growth, primary energy consumption, and globalization for the period between 1990Q1 and 2019Q4. The outcomes of the Fourier ARDL long-run estimates indicate that (i) both energy productivity and globalization have a negative effect on carbon emissions in Germany, and (ii) both economic growth and primary energy consumption have positive effects on carbon dioxide emissions. These outcomes provide significant policy insights to EU members with respect to reducing their reliance on Russian energy imports amidst the rising energy bills and ongoing geopolitical war with Ukraine while increasing investments to realize their energy turnaround policy objectives.
Keywords: Germany; Fourier ARDL; Fourier ADL cointegration; Fourier ADF unit root; energy productivity; environmental degradation; globalization; primary energy consumption; growth; CARBON EMISSIONS EVIDENCE; CO2 EMISSIONS; ECONOMIC-GROWTH; KUZNETS CURVE; DIOXIDE EMISSIONS; RENEWABLE ENERGY; ECO-INNOVATION; CONSUMPTION; DECOMPOSITION; Science & Technology - Other Topics; Environmental Sciences & Ecology